Pojok Baca Kreatif : Upaya Meningkatkan Minat Baca Siswa SD dengan Media Buku Interaktif - Wahyuddin Wahyuddin; Ahmad Kautsar; Deviyantoro Deviyantoro; Anizir Anizir; Denny Kurnia (LPPM Universitas Informatika dan Bisnis Indonesia, 2025)
This community service activity aims to increase students' interest in reading at SDN Bulakan II Cilegon through an approach that involves students, teachers and the use of technology. This program is implemented by providing creative reading corner facilities, holding joint reading activities at school. The results of this activity showed a significant increase in students' reading interest, more students were involved in reading activities and book discussions. In addition, parent and teacher involvement has also increased, with them better understanding the importance of supporting their children's reading habits. The use of technology in literacy activities such as e-book applications and digital learning platforms has also proven effective in attracting student interest. With this program, it is hoped that students' interest in reading can continue to develop and contribute to the development of their literacy skills in the future. This program also has a positive impact on improving the quality of literacy learning based on collaboration and interactivity between students, teachers and parents.